Propaganda Budaya sebagai Moral Warfare: Musik Populer dan Resistensi Etik di Era Peperangan Asimetris - Al Fauzi, Muhammad Ridwan; Akmal, Mula; Cempaka Timur, Fauzia Gustarina; Widodo, Pujo (Interdependence Journal of International Studies, 2025)
Entering the era of asymmetric warfare signifies that power is no longer confined to military capability but to the construction of moral legitimacy and cultural narratives. This transformation defines moral warfare, a conflict fought through values, ethics, and symbols that shape public consciousness. This research examines how cultural propaganda, particularly popular music, functions as an instrument of moral warfare and ethical resistance to ideological hegemony. Using integrative qualitative analysis of literature (2020–2025) on war ethics, soft power, and cultural hegemony, the study reveals that popular music influences collective moral awareness through artistic representation, lyrics addressing social issues, and digital dissemination. As a form of counter-hegemonic moral discourse, music integrates ethical, aesthetic, and communicative dimensions, enabling cultural transformation and serving as a non-military defence strategy based on moral persuasion and shared human values.